The prisioners of Malta (Asira'n-e-Malta) : the heart-rending tale of Muslim freedom fighters in British period - Miyan, Sayyid Muhammad, 1903-1975 (New Delhi : Jamiat Ulama-i-Hind, 2005)
On the imprisonment of Shaikhulhind Mahmud Hasan, 1851-1920 and Sayyid Husain Ahmad Madni, 1878-1957 and their companions, Muslim religious scholars by the British rulers in the Malta prison camps
Includes bibliographical references and index
Keywords: Hasan, Mahmud, -- Shaikhulhind, -- 1851-1920 -- Imprisonment; Madni, Sayyid Husain Ahmad, -- 1878-1957 -- Imprisonment; Politicians -- India -- Biography; Nationalists -- India -- Biography; Political prisoners -- Malta -- Biography